UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN TUMBUHAN AKAR KAIK-KAIK (Uncaria cordata (Lour) Merr) TERHADAP MENCIT PUTIH JANTAN (Mus musculus L) - Noveri Rahmawati; Nur Indah Melati; Meiriza Djohari (Jurnal Penelitian Farmasi Indonesia, 2021)
Research on the acute toxicity test of the ethanol extract of kaik-kaik (Uncaria cordata (Lour) Merr) leaves has been carried out on male white mice (Mus musculus L.). This study aims to determine the effects of acute and delayed toxicity of the ethanol extract of kaik- kaik root (Uncaria cordata (Lour) Merr) leaves by determining the LD50 value. The experimental animals were divided into 4 groups, namely the negative control group (NaCMC), and the ethanol extract group of kaik-kaik root leaves with doses of 200, 1000, and 5000 mg / KgBB. The results showed that the LD50 value was> 5000 mg / kg BW and was included in the practical non-toxic category. In the observation, there were no tremors, seizures, salivation, diarrhea, lethargy, weakness, sleep, and coma in each experimental animal.